2015
DOI: 10.1371/journal.pone.0112969
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of RNA Helicase DDX3 with HIV-1 Rev-CRM1-RanGTP Complex during the HIV Replication Cycle

Abstract: Molecular traffic between the nucleus and the cytoplasm is regulated by the nuclear pore complex (NPC), which acts as a highly selective channel perforating the nuclear envelope in eukaryotic cells. The human immunodeficiency virus (HIV) exploits the nucleocytoplasmic pathway to export its RNA transcripts across the NPC to the cytoplasm. Despite extensive study on the HIV life cycle and the many drugs developed to target this cycle, no current drugs have been successful in targeting the critical process of vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 64 publications
(69 reference statements)
0
16
0
Order By: Relevance
“…In addition, DDX3 is essential for the nuclear export of the human immunodeficiency virus 1 (HIV-1) protein Rev and is, therefore, also a potential therapeutic target in the treatment of HIV infections 35,36. Understanding the cellular mechanisms behind increased nuclear retention of DDX3 may facilitate the development of therapies specifically targeting the export function of DDX3 37. In addition, nuclear DDX3 could serve as a prognostic and potentially therapeutic biomarker for selecting cancer patients that may benefit from treatment with DDX3 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, DDX3 is essential for the nuclear export of the human immunodeficiency virus 1 (HIV-1) protein Rev and is, therefore, also a potential therapeutic target in the treatment of HIV infections 35,36. Understanding the cellular mechanisms behind increased nuclear retention of DDX3 may facilitate the development of therapies specifically targeting the export function of DDX3 37. In addition, nuclear DDX3 could serve as a prognostic and potentially therapeutic biomarker for selecting cancer patients that may benefit from treatment with DDX3 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, both our proposed physical transport mechanism and our mathematical approach are novel. Most previous modeling work on the NPC has focused on atomistic (2,(43)(44)(45) and coarse-grained simulations (8,12,33,(46)(47)(48)(49)(50). This has illuminated many of the finer points of nuclear transport, but the detailed nature of this work makes it difficult to draw general conclusions about the driving force behind cargo translocation.…”
Section: Comparison To Previous Modelsmentioning
confidence: 99%
“…The expression of DDX3X was also activated at the intermediate HIV infection stage. Therefore, we suggested that DDX3X could regulate HIV replication through MIR139-5p regulations [ 98 , 99 ].…”
Section: Discussionmentioning
confidence: 99%